Determinants of E-Government Implementation Based on Technology Acceptance Model - Nurkholis, Nurkholis; Anggraini, Rosalina Yuri (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2020)
This study aims to examine Technology Acceptance Model (TAM) on the implementation of E-Government. Data for this study were collected through a questionnaire survey on the people of Malang City who have used E-Government services. Structural model analysis was performed using smartPLS. The results showed that intention was the main determinant of the use of E-Government services. The determining factor of intention to use E-Government services is positive attitude towards E-Government. Other factors such as system quality, its ease of use, and quality of information do not affect people’s interest in using E-Government services. In other words, E-Government application developed by the City Government has been deemed not easy enough to be applied and not informative enough to meet the information needs of the community. This is a challenge for the City Government to be able to improve and develop the quality of systems and information from its E-Government services so that people are increasingly interested in applying it, for the realization of Malang as a smart city.